IJCM_112A: Impact of competitive spirit on weight, waist circumference and HbA1c among the followers of Dixit Lifestyle participating in 90 Days weightloss and Diabetes Reversal Challenge - Dixit Jagannath (Wolters Kluwer Medknow Publications, 2024)
Background: Author has initiated World free of obesity and diabetes campaign since 2013. This lifestyle suggests taking only two meals in a day and go for any cardio exercise for 45 minutes at a stretch every day. This lifestyle is showing great results in weight loss and diabetes prevention/remission. Through the campaign 90 days weight loss and diabetes reversal challenge was organized from 1t August to 31st October 2023. Objectives: 1) To find out the effect of competitive spirit on weight and waist circumference among the participants 2) To find out the effect of competitive spirit on HbA1c and doses of diabetes medicines Methodology: Through messages on social media people were informed about the 90 days weight loss and diabetes reversal challenge. To join the challenge it was mandatory to submit there latest HbA1c and fasting insulin report, weight (Kg) and waist circumference (cm). Participants were categorized and added to non diabetic, prediabetic and diabetic WhatsApp groups having senior coordinators who monitored their progress. Members had to post screen shot of daily exercise and photo of daily meals. Weekly quizzes and various competitions were organized. Members filled daily google form and progress tracker at the end challenge with all parameters. Results: Out of 648 members 544 submitted all data at the end of three months which included 68 non diabetics, 253 prediabetics and 223 diabetics. Average weight loss was 4.12 Kg and waist circumference loss was 2.29 inches. Average HbA1c reduction was 0.428 gm%. 80 diabetics converted to prediabetic status and 10 to non diabetic status. 53 prediabetics became non diabetics. In 44 diabetics medicines were reduced and in 16 they were stopped. Conclusion: Competitive spirit while following Dixit Lifestyle has shown great results as regards weight loss, inch loss and HbA1c reduction.